EMBRYONIC DEVELOPMENT OF CLARIAS BATRACHUS UNDER THE INFLUENCE OF AERATION AND WATER FLOW - Rahman, Sk. Mustafizur; Habib, Md. Ahasan; Hossain, Quazi Zahangir; Siddiqui, Md. Noman; Rahman, Md. Mostafizur; Ahsan, Md. Nazmul (Ecoprint: An International Journal of Ecology, 2013)
Specific investigation on the time (h) required for catfish, Clarias batrachus, embryos to reach various early developmental stages were carried out under different experimental conditions. Five hundred fertilized eggs were incubated in tray (28ºC–30.5ºC) with continuous water flow and aeration (T1), with only continuous water flow (T2) or aeration (T3) and without continuous water flow and aeration (T4). Fertilized embryos hatched successfully in all treatments except for T4. Time requirements for 2-cell, 4-cell, 8-cell, morula, germinal ring, yolk-plug, twisting movement, prehatching and hatching were comparable for all treatments. However, developmental speed was ceased from yolk-plug stage for T4. Time requirements for two-cell, four-cell, eight-cell, morula, germinal ring, yolk-plug, twisting movement, and hatching were 0.43, 0.48, 0.53, 3.52, 6.07, 8.50, 15.04, 20.08, and 21.40 h, respectively for T1; 0.44, 0.47, 0.51, 3.49, 6.10, 8.51, 15.13, 20.19, and 21.56 h, respectively for T2; 0.50, 0.53, 0.59, 3.52, 6.13, 8.53, 15.11, 20.18, and 22.13 h, respectively for T3. Fertilized eggs of C. batrachus incubated in tray with only aeration (T3) is sufficient for successful hatching and could be cost-effective for hatchery operation. DOI: http://dx.doi.org/10.3126/eco.v18i0.9395 Ecoprint: An International Journal of Ecology Vol. 18, 2011 Page: Uploaded date: 12/20/2013